Review on the status of theory and research of social media studies in Malaysia: a conceptual paper - A. Rahman, Nur Atikah; Hassan, Md. Salleh; Osman, Mohd Nizam; Waheed, Moniza (International Organization of Scientific Research, 2017)
In the recent years, the literature indicated that adoption and consequences of using social media on the users and society has become a popular topic among the communication scholars. However, past studies also show that prior efforts in discussing on the stature and scholarship of social media research in Malaysia is scarce. Thus, the purpose of this conceptual paper is to review on the theoretical patterns and research trends of social media related studies on Malaysian users. In particular, the method used is based on literature reviews in chronological order concerning new media, social media and research trends analyses from journal articles, thesis proceedings and conferences, book and more. A framework of analysis was generated to identify the frequency and occurrences in theoretical application, research topic areas, methodological approaches, types of contents, social media medium of interest and research developmental phases of social media studies. The study ends with summaries and recommendations to utilise comprehensive content analyses of communication and media journals in Malaysia to trace the theoretical trends and research patterns pertaining to social media research.